Current State of Azerbaijan's Gas & Oil Cooperation with Europe: Opportunities and Challenges - Gubad Ibadoghlu (ZBW - Leibniz Information Centre for Economics, 2024)
The paper provides a comprehensive analysis of Azerbaijan's energy cooperation with Europe. It covers the supply of fossil fuels (oil and gas) and green energy, examining both retrospective and prospective dimensions. The analysis includes production levels, transport infrastructure, potential opportunities in this sector, and challenges, calling for further investigation. The article also assesses possible development scenarios and prospects for gas, oil, and renewable energy sources in Azerbaijan's energy sector. The first part covers the current status and prospects of Azerbaijan's gas production, consumption, transportation, and export. The second and third parts analyze and evaluate the status of the oil and renewable energy sectors, respectively.
Keywords: 330